Simplified Deadbeat Predictive Torque Control Based on Discrete Space Vector Modulation for Driving an Open-End Winding Permanent Magnet Synchronous Motor - Lee, Hyung Woo; Hwang, Jun Ho; Lee, Kyo Beum (IEEJ Journal of Industry Applications, 2024)
This study proposes a simplified deadbeat (DB) predictive torque control (PTC) strategy for driving an open-end winding permanent magnet synchronous motor (OEW-PMSM) to reduce the torque and current ripple. The torque and current ripple are large because the conventional finite set PTC (FS-PTC) uses only one voltage vector in the sampling period. To avoid these problems, a simplified PTC strategy based on discrete space vector modulation (DSVM) is proposed to split the voltage vector into a virtual voltage vector and select the optimal voltage vector. Furthermore, the DB method is used to estimate the reference voltage angle and to thereby select an area that includes the candidate voltage vectors to reduce the computational burden. Among these candidate voltage vectors in the selected area, the optimal voltage vector can be selected by calculating the cost function. Therefore, one or more voltage vectors are used in the sampling period, reducing the torque and current ripple. The effectiveness of the proposed strategy is verified through simulation and experimental results.
Keywords: Current ripples; Discrete space vector modulation; Dual inverters; Open-end winding permanent magnet synchronoi motor; Open-end windings; Permanent Magnet Synchronous Motor; Predictive torque control; Predictive torque controls; Torque ripples; Voltage vectors; dual inverter; open-end winding permanent magnet synchronous motor (OEW-PMSM); predictive torque control (PTC)